1977
DOI: 10.1002/j.1551-8833.1977.tb06705.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of a Water Softening Sludge Into Pozzolanic Paving Material

Abstract: A paper contributed to and selected by the JOURNAL, authored by Ronald D. Watt, res. engr., environ, equipment div., FMC Corp. (Associate Member, AWWA), Itasca, III.; and Donald I. Angelbeck (Active Member, AWWA), assoc. prof., civ. engr. dept., Univ. of Toledo, Toledo, Ohio.Recent and future environmental regulations created a critical need for new environmentally sound sludgedisposal techniques in the water-supply field. Several sludge-disposal concepts utilizing sludge as a raw material for product manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The beneficial use of lime sludge may eliminate the disposal cost and could potentially generate revenue for water utilities. Some potential beneficial uses of lime sludge include subsurface filling, cement manufacturing, , mining industry-related applications, soil pH regulation, feedstock for new composite materials, , and as a replacement for ground limestone in the wet scrubbing process. Reports on the properties of lime sludge samples and experimental data have indicated that lime sludge could be a suitable replacement for limestone in FGD systems. ,, Among these studies are three major reports that provided data directly from successful utilization of lime sludge for FGD in power plant tests.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial use of lime sludge may eliminate the disposal cost and could potentially generate revenue for water utilities. Some potential beneficial uses of lime sludge include subsurface filling, cement manufacturing, , mining industry-related applications, soil pH regulation, feedstock for new composite materials, , and as a replacement for ground limestone in the wet scrubbing process. Reports on the properties of lime sludge samples and experimental data have indicated that lime sludge could be a suitable replacement for limestone in FGD systems. ,, Among these studies are three major reports that provided data directly from successful utilization of lime sludge for FGD in power plant tests.…”
Section: Introductionmentioning
confidence: 99%